THE EFFECTS OF DANCE AEROBICS ON PHYSICAL FITNESS - Dejan Stošić; Jasmin Gračanin; Nebojša Trajković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
In addition to traditional forms of daily physical exercise, different types of physical exercises appeared, which are quite interesting and more appealing than the usual forms of exercise. Aerobic dance is one of those types of physical exercise that can positively influence the development of some of the components of physical fitness. The aim of this study was to examine the scientific research concerning the effects of aerobic dance on physical fitness with people aged 20 to 39. The conclusion is that aerobic dance can contribute to the improvement of certain components of physical fitness and that the greatest impact aerobic dance has on the cardiovascular system and body composition